Broadening consent—and diluting ethics?. Issue 2 (30th January 2009) - Hofmann, B
Abstract : Biobank research is potentially fruitful. It is argued that broad consent is acceptable for future research on biological material because a) the benefit is high, b) it pays respect to people's autonomy, c) it is consistent with current practices and d) because the risk is low. Furthermore, broad consent should be allowed if information is handled safely, people can withdraw and expanded research should be approved by an ethics review board. However, these arguments are flawed and the criteria for broad consent are either too restrictive to allow any research or fail to address important challenges with biobank research. Broad consent for biobank research can hide substantial ethical challenges and threaten trust in research. This does not mean that biobank research should be abandoned or that people cannot authorise future research on donated biological material.